Cats & dogs. [videorecording (DVD)] The revenge of Kitty Galore - Peyton, Brad, 1979-; O'Donnell, Chris; Duncan, Michael Clarke; Nolte, Nick; Midler, Bette; Applegate, Christina, 1971-; Harris, Neil Patrick, 1973-; Hayes, Sean, 1970- (Warner Home Video, 2010)
In the eternal battle between cats and dogs, one crazed feline has taken things a paw too far. Former elite agent Kitty Galore has gone rogue and plans to unleash a diabolical device designed to not only bring her canine enemies to heel but also to take down her former kitty comrades and make the world her scratching post. Faced with this dire threat, cats and dogs must work together for the first time ever to save themselves and their beloved humans from global cat-astrophe.